Transformasi Digital Administrasi Rawat Jalan melalui Implementasi SIMRS di RS Aisyiyah - Sela Maharani; Ahmad Farid (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
The digital transformation in healthcare encourages hospitals to integrate information systems to improve service efficiency, data accuracy, and coordination across units. Aisyiyah Hospital has implemented the Hospital Management Information System (SIMRS) in all service units, including the outpatient department. However, its implementation still encounters several obstacles that affect the smoothness of administrative processes and the quality of patient services. This study employed a qualitative approach with a descriptive explorative design. Data were collected through semi-structured interviews with outpatient administrative staff who directly operate SIMRS in daily activities, supported by field observations of workflow and system performance. Informants were selected using purposive sampling based on their experience and operational involvement. The data were analyzed using a narrative thematic method to identify key barriers, impacts, and adaptive solutions. The findings indicate that SIMRS implementation in the outpatient unit of Aisyiyah Hospital has not yet been optimal. Major challenges include limited network and hardware infrastructure, uneven human resource readiness, and the persistence of manual work culture. These barriers lead to delays in service delivery, data entry errors, and weak inter-unit data integration. To address these issues, staff coordinate with the IT team during system disruptions, use manual recording as a temporary measure, and conduct internal peer learning to improve system utilization. The results highlight that the success of SIMRS implementation depends not only on technological capability but also on infrastructure readiness, user competence, and organizational work culture transformation. System optimization requires managerial support through infrastructure enhancement, structured technical training, and consistent supervision of system use in each unit to ensure that SIMRS functions effectively in supporting patient care.